Ankle and Lower Leg Injuries in Professional Baseball Players. Issue 4 (16th October 2019) - Lucasti, Christopher; Dworkin, Myles; Warrender, William; Pedowitz, David; Winters, Brian; Ciccotti, Michael
Category: Ankle, Sports, Trauma Introduction/Purpose: The purpose of this study was to determine the injury characteristics of ankle and lower leg injuries in professional baseball players during the 2011-2016 seasons by utilizing the Major League Baseball (MLB) injury surveillance system. Methods: Our study is a descriptive epidemiological evaluation through a retrospective review from the MLB Health and Injury Tracking System (HITS) since its implementation in 2011. We included any professional baseball player (Major League and Minor League) who was identified as having an ankle or lower leg injury from January 1, 2011 through February 28th, 2017.Over the study period there were a total of 4, 756 injuries of which 763 (16.0%) occurred in the Major League and 3, 993 (84.0%) occurred in the Minor League. Results: The average number of days missed for all players was 27.8 days (+/-141.4 days) with a median of 3 days. From 2011 through 2016 it was estimated that there were 414, 912 athlete exposures (AEs) in Major League Baseball and 1, 796, 607 AEs in the Minor Leagues. Of the 4, 756 injuries recorded, 550 (11.6%) took place during the Major League regular season and 3, 320 (69.8%) took place during the Minor League regular season. Major League injuries, however, were 1.7 times more likely to require surgery (p < .001). Additionally, rates of injury to the lower leg were stratified by position with infield players experiencing injuries at a 1.6 times greater rate than any other position (p < .001). Conclusion: In conclusion, the data from this study represents the only epidemiological study to focus primarily on lower leg injuries in professional baseball players utilizing an injury surveillance system developed by MLB.